Intervensi Acceptance and Commitment Therapy (ACT) untuk Menurunkan Gejala Academic Burnout - Rani, Cut Athika; Cut Nurul Kemala (Universitas Darul Ulum, 2025)
Gifted-class students are vulnerable to academic burnout due to high academic demands. This intervention aimed to reduce burnout symptoms by enhancing psychological flexibility and mindfulness through Acceptance and Commitment Therapy (ACT). The hypothesis was that ACT would reduce academic burnout and improve psychological flexibility and mindfulness. Five participants which is high school students (aged 16–17) with high burnout scores based on the MBI-SS completed six online group sessions. A one-group pre-test–post-test quasi-experimental design was used. Based on pretest dan posttest results showed a significant reduction in academic burnout and psychological inflexibility, as well as an increase in mindfulness scores post-intervention. This study represents one of the first attempts to apply ACT among gifted-class students in Indonesia, providing a novel contribution to the development of acceptance-based interventions for addressing high academic pressure in this population These findings support ACT's effectiveness as a psychological intervention for adolescents under academic stress.